A Case Analysis On Berjaya Group Berhad : Berjaya Hotels And Resorts - Kiguta, Luiza Wanjiku (2005)
This dissertation looks at strategies designed to increase the competitive advantage of Berjaya land Berhad's - Hotels and Resorts positioning that would allow it to adapt to the momentum of growth with the tourism industry in Malaysia.